Little Hankel operators on the Bergman space - Namita Das; Pabitra Kumar Jena (Arab Journal of Mathematical Sciences, 2016)
In this paper we obtain a characterization of little Hankel operators defined on the Bergman space of the unit disk and then extend the result to vector valued Bergman spaces. We then derive from it certain asymptotic properties of little Hankel operators.